Veno-Venous Extracorporeal Membrane Oxygenation Use in the Treatment of Bleomycin Pulmonary Toxicity. Issue 2 (March 2017) - Shah, Aakash; Pasrija, Chetan; Kronfli, Anthony; Wehman, Brody; Griffith, Bartley P.; Sanchez, Pablo G.; Garcia, Jose P.; Kon, Zachary N.
Abstract : Abstract: Pulmonary toxicity is a devastating complication of bleomycin chemotherapy. This insult is likely exacerbated by the free radical injury induced by high inspired oxygen content, which is required to support these patients. Traditional treatment consists of high-dose corticosteroids. We report the case of a 45-year-old man who developed bleomycin pulmonary toxicity, which failed to respond to treatment with high-dose corticosteroids. We used protective mechanical ventilatory settings while supported on veno-venous extracorporeal membrane oxygenation using a bicaval dual-lumen, single cannula system to allow for lung recovery. This case demonstrates the feasibility of using veno-venous extracorporeal membrane oxygenation to treat bleomycin pulmonary toxicity in a patient who has failed traditional therapy.